(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
According to recent studies, statistics indicate that more than 10 million people are exposed to brain injuries in all countries of the world annually. Brain injury patients, as well as their families, are usually concerned with the expectations and possible complications as a result of the injury and the extent of their recovery, and they request this information from nurses. The cognitive level of nurses plays an essential role in providing care to brain injury patients, which reflects negative outcomes if perceptions are inaccurate. Most deaths from traumatic brain injury are related to massive hemorrhage, which is preventable. Its percentage increases before the patient arrives at the hospital, and therefore attention must be paid to the (C)ABCDE guide to reduce the possible consequences.